Control of sulfur partitioning between primary and secondary metabolism in Arabidopsis - Kopriva, Stanislav; Mugford, Sarah G.; Baraniecka, Patrycja; Lee, Bok-Rye; Matthewman, Colette A.; Koprivova, Anna (Frontiers in Plant Science, 2012)
Sulfur is an essential nutrient for all organisms. Plants are able to take up inorganic sulfate and assimilate it into a range of bioorganic molecules either after reduction to sulfide or activation to 3’-phosphoadenosine 5’-phosphosulfate. While the regulation of the reductive part of sulfate assimilation and the synthesis of cysteine has been studied extensively in the past three decades, much less attention has been paid to the control of synthesis of sulfated compounds. Only recently the genes and enzymes activating sulfate and transferring it onto suitable acceptors have been investigated in detail with emphasis on understanding the diversity of the sulfotransferase gene family and the control of partitioning of sulfur between the two branches of sulfate assimilation. Here the recent progress in our understanding of these processes will be summarised.